The regional distribution and correlates of an entrepreneurship-prone personality profile in the United States, Germany, and the United Kingdom: A socioecological perspective - Martin Obschonka; Eva Schmitt-Rodermund; Rainer K. Silbereisen; Samuel D. Gosling; Jeff Potter (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
In recent years the topic entrepreneurship has become a major focus in the social sciences, with renewed interest in the links between personality and entrepreneurship. Taking a socioecological perspective to psychology, which emphasizes the role of social habitats and their interactions with mind and behavior, we investigated regional variation in and correlates of an entrepreneurship-prone Big Five profile. Specifically, we analyzed personality data collected from over half a million U.S. residents (N = 619,397) as well as public archival data on state-level entrepreneurial activity (i.e., business-creation and self-employment rates). Results revealed that an entrepreneurship-prone personality profile is regionally clustered. This geographical distribution corresponds to the pattern that can be observed when mapping entrepreneurial activity across the U.S.. Indeed, the state-level correlation (N = 51) between an entrepreneurial personality structure and entrepreneurial activity was positive in direction, substantial in magnitude, and robust even when controlling for regional economic prosperity. These correlations persisted at the level of U.S. Metropolitan Statistical Areas (N = 15) and were replicated in independent German (N = 19,842; 14 regions) and British samples (N = 15,617; 12 regions). In contrast to these profile-based analyses, an analysis linking the individual Big Five dimensions to regional measures of entrepreneurial activity did not yield consistent findings. Discussion focuses on the implications of these findings for interdisciplinary theory development and practical applications.
Keywords: 330